2009
DOI: 10.1182/blood-2008-09-177741
|View full text |Cite
|
Sign up to set email alerts
|

Limited ability of humoral immune responses in control of viremia during infection with SIVsmmD215 strain

Abstract: We investigated the impact of rhesus macaque (RM) B-cell depletion before inoculation with the isolate SIVsmmD215. Seven RMs were treated every 3 weeks with 50 mg/kg of an anti-CD20 antibody (rituximab) starting 7 days before inoculation for 2 (n ‫؍‬ 4) and 5 (n ‫؍‬ 3) months. Four control animals received no antibody. Three animals were completely depleted of CD20 ؉ B cells, but 4 were only partially depleted of CD20 cells in the LNs and intestine. The decrease in antibody production was consistent with the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(41 citation statements)
references
References 55 publications
2
33
1
Order By: Relevance
“…In our previous study of CD20 ϩ B-cell depletion in RMs infected with SIVsmmD215, we observed that the ablation of humoral immune responses was predicted by the efficacy of B-cell depletion in tissues (18). We therefore examined the changes in the B-cell populations in tissues in rituximab-infused and control AGMs.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In our previous study of CD20 ϩ B-cell depletion in RMs infected with SIVsmmD215, we observed that the ablation of humoral immune responses was predicted by the efficacy of B-cell depletion in tissues (18). We therefore examined the changes in the B-cell populations in tissues in rituximab-infused and control AGMs.…”
Section: Resultsmentioning
confidence: 99%
“…However, these studies used strains that are highly resistant to neutralization (SIVmac251 and SIVmac239), making it difficult to assess the role that antibodies have in controlling SIV replication and disease progression. Moreover, our recent results suggested a limited impact of humoral immune responses in controlling replication of a neutralization-sensitive SIVsmm strain in rhesus macaques (18).…”
Section: Ccr5mentioning
confidence: 99%
“…An important question remaining is the degree to which T-bet + B cells and derived antibodies contribute to control of viremia during HIV and other viral infections. Indeed, while a murine study demonstrated the requirement of T-bet + B cells to control chronic LCMV viremia to low levels (6), the role of B cells and Ig in ongoing control of HIV/SIV remains controversial (74)(75)(76)(77)(78). However, it is highly likely that an efficacious HIV vaccine will need to induce HIV Env-specific broadly neutralizing antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…Cells were filtered through nylon bags and washed with RPMI medium (Cellgro, Manassas, VA) containing 5% heat-inactivated newborn calf serum, 0.01% penicillin-streptomycin, 0.01% L-glutamine, and 0.01% HEPES buffer, as previously described (48,51). Lymphocyte separation from pinch biopsy specimens was done as previously described (17,50,51,55). Briefly, intestinal biopsy specimens were digested using EDTA followed by collagenase, and cells were then isolated using Percoll density gradient centrifugation (50,51,55).…”
Section: Animalsmentioning
confidence: 99%